Near-native state imaging by cryo-soft-X-ray tomography reveals remodelling of multiple cellular organelles during HSV-1 infection. - Kamal L Nahas; Viv Connor; Katharina M Scherer; Clemens F Kaminski; Maria Harkiolaki; Colin M Crump; Stephen C Graham (PLoS Pathogens)
Herpes simplex virus-1 (HSV-1) is a large, enveloped DNA virus and its assembly in the cell is a complex multi-step process during which viral particles interact with numerous cellular compartments such as the nucleus and organelles of the secretory pathway. Transmission electron microscopy and fluorescence microscopy are commonly used to study HSV-1 infection. However, 2D imaging limits our understanding of the 3D geometric changes to cellular compartments that accompany infection and sample processing can introduce morphological artefacts that complicate interpretation. In this study, we used soft X-ray tomography to observe differences in whole-cell architecture between HSV-1 infected and uninfected cells. To protect the near-native structure of cellular compartments we used a non-disruptive sample preparation technique involving rapid cryopreservation, and a fluorescent reporter virus was used to facilitate correlation of structural changes with the stage of infection in individual cells. We observed viral capsids and assembly intermediates interacting with nuclear and cytoplasmic membranes. Additionally, we observed differences in the morphology of specific organelles between uninfected and infected cells. The local concentration of cytoplasmic vesicles at the juxtanuclear compartment increased and their mean width decreased as infection proceeded, and lipid droplets transiently increased in size. Furthermore, mitochondria in infected cells were elongated and highly branched, suggesting that HSV-1 infection alters the dynamics of mitochondrial fission/fusion. Our results demonstrate that high-resolution 3D images of cellular compartments can be captured in a near-native state using soft X-ray tomography and have revealed that infection causes striking changes to the morphology of intracellular organelles.